Critical perspectives on ageing societies - Bernard, Miriam 1954-; Scharf, Thomas ca. 20./21. Jh (Ageing and the lifecourse, 2007)
This important book brings together some of the best known international scholars working within a critical gerontology perspective. Together, they review and update our understanding of how the field has developed over the last twenty-five years and, through the lens of 'passionate scholarship', provide a challenging assessment of the complex practical and ethical issues facing older people, and those who conduct research on ageing, in the 21st century. The contributions extend the critical gerontological approach conceptually, methodologically and practically. They offer close and scholarly analysis of policies affecting the lives of older people and provide insights into why research is done in particular ways. Special attention is paid to feminist contributions and new approaches to working in partnership with older people; age discrimination and ageism; the impact of neo-liberal policies and the passage of various human rights instruments; the re-medicalisation of later life; the participation of older people in research; and justice between generations. The editors and contributors offer suggestions for promoting change, and an exciting set of visions and perspectives for the renewal and development of critical gerontology in the years ahead. Critical Perspectives on Ageing Societies will be a valuable resource for all students, academics and practitioners interested in ageing and the life course